Determining the microstructure of soft sediments by automatic analysis of scanning electron microscope images of the Dead Sea fault seismites - Alona Balaban‐Fradkin; Shalev Siman‐Tov; Shmuel Marco; Eyal Heifetz (The Depositional Record, 2022)
Abstract The Dead Sea seismites comprise the worlds longest record of earthquakes. The seismites appear as deformed layers enclosed between undeformed layers of alternating millimetre‐thick laminae with annual pairs of winter detritus and summer evaporitic aragonite. Understanding the physical conditions that govern their formation will promote the recovery of the causative earthquake properties from the deformation character. The first step towards this goal is understanding the microscopic structure of the seismites. To this end, scanning electron microscope images of the Dead Sea Basin sediments were analysed to extract their pore and grain sizes. The implementation of image processing techniques to determine the microscopic‐scale physical properties of the deformed and undeformed layers are in general agreement with results from classical labour‐intensive instruments. However, the image processing analyses provide more detailed unbiased information. A MATLAB‐based code has been developed as a ready‐to‐use package, which can be easily implemented on any other occurrence of soft sediment outcrops to analyse sediment microscopic‐scale physical properties from scanning electron microscope images.